Optoelectronics and fiber optic technology - Tricker, Ray (Raymond L.)
Topical areas such as optoelectronics in LANs and WANs, cable TV systems, and the global fiber-optic highway make this book essential reading for anyone who needs to keep up with the technology of modern data communications. *Covers selection and application of the key technologies*A down-to-earth introduction to a cutting-edge technology*Covers all the main engineering applications with a minimum of maths.